A Freestanding Stretchable and Multifunctional Transistor with Intrinsic Self‐Healing Properties of all Device Components. Issue 2 (12th December 2018) - Khatib, Muhammad; Huynh, Tan‐Phat; Deng, Yunfeng; Horev, Yehu David; Saliba, Walaa; Wu, Weiwei; Haick, Hossam
Abstract: A flexible and stretchable field‐effect transistor (FET) is an essential element in a number of modern electronics. To realize the potential of this device in harsh real‐world conditions and to extend its application spectrum, new functionalities are needed to be introduced into the device. Here, solution‐processable elements based on carbon nanotubes that empower flexible and stretchable FET with high hole‐mobility ( µ h ≈ 10 cm 2 V −1 s −1 ) and relatively low operating voltages (<8 V) and that retain self‐healing properties of all FET components are reported. The device has repeatable intrinsic and autonomic self‐healing ability, namely without use of any external trigger, enabling the restoration of its electrical and mechanical properties, both after microscale damage or complete cut of the device—for example by a scissor. The device can be repeatedly stretched for >200 cycles of up to 50% strain without a significant loss in its electrical properties. The device is applicable in the form of a ≈3 µm thick freestanding skin tattoo and has multifunctional sensing properties, such as detection of temperature and humidity. With this unprecedented biomimetic transistor, highly sustainable and reliable soft electronic applications can be introduced. Abstract : Autonomous self‐healing transistors with multifunctional properties for wearable electronics were introduced using the strategy of combining carbon nanotubes with stretchable and self‐healing polyurethane.